Phasing analysis on DRO with impulsive maneuver - Fu, Honglan; Wang, Ming; Zhang, Hao (Frontiers in Astronomy and Space Sciences, 2023)
The Cis-Lunar periodic orbit has unique dynamic characteristics. Among them, the distant retrograde orbit has long-term stability and is one of the ideal candidate deployment orbits for the Cis-Lunar space station and even the deep space exploration transfer station. The flight process of space station on-orbit construction, material supply, spacecraft monitoring and other tasks includes orbiting, rendezvous, and docking. By shortening the relative distance between spacecrafts through phasing, suitable initial conditions can be created for these operations. In this paper, the characteristics of two-impulse phasing orbit on DRO are summarized, and the phasing ability is analyzed globally. Based on these analyses, a phasing optimization problem is presented and solved. According to the dynamic characteristics of DRO, a DRO multi-impulse phasing rolling solving method is presented. To be closer to the actual mission scenario, the orbit determination error is also considered in this method. The simulation analysis is carried out under the circular restricted three-body problem (CR3BP) dynamic model and the ephemeris model. Compared with the results of two-impulse phasing, this method can reduce the offset of the end position of the DRO phasing orbit from the order of hundreds of kilometers to the order of tens of kilometers. This result meets the requirements of relative distance for subsequent spacecraft operations. The total pulse requirement of this phasing method under the two models is within a reasonable range, which is feasible.